PENGARUH CITRA MEREK DAN KEPERCAYAAN MEREK TERHADAP KEPUASAN PELANGGAN SERTA DAMPAKNYA TERHADAP LOYALITAS MEREK SEPEDA MOTOR MEREK HONDA - NURFADILA, NURFADILA (Fakultas Ekonomi Universitas Tadulako, 2015)
Independent variables used in this study are brand image and brand trust, while the dependent variable is customer satisfaction and brand loyalty. The type of research used in this research is descriptive causal method. Samples used in this study were as many as 97 respondents with the form of sampling using techniques Purposive Sampling and Accidental Sampling. Data analysis method used in this research is path analysis method. Result of research indicate that brand image influence to customer satisfaction, brand trust influence to customer satisfaction, brand image does not influence to brand loyalty, brand trust influence to brand loyalty and customer satisfaction influence to brand loyalty.